A Democratização Educativa como Direito e Meio Para Uma Globalização Humanizada (Glocalism: Journal of Culture, Politics and Innovation, 2022)
The meanings of democratic participation in educational contexts are discussed in this text in the counter-hegemonic globalization weave of possibilities. The methodological pathway establishes a dialog among documentary and bibliographic studies and empirical data on the participation under the theoretical perspective of complex thinking and democratic justice. On the trails of counter-hegemonic globalization, conceptual argumentation and guidelines of educational and childhood policies indicate that participation is an essential element of praxis. In this context, participation acts as principle, strategy and result in the multidimensional configuration of emancipatory learning and the right to democratic education as a possibility of ensuring sustainability of human and planetary life conditions.
Keywords: educational policies; participation; democracy; childhood rights; globalization